Developing an integrated model of TQM and HRM on KM activities - Ooi, Keng Boon; Teh, Pei Lee (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to develop an integrated model of total quality management (TQM) and human resource management (HRM) to elucidate the influence of TQM and HRM practices on knowledge management (KM) activities. Design/methodology/approach – The theory of KM serves as a starting-point to develop the integrated conceptual model linking TQM and HRM aspects. Based on an extensive review of the current literature, three practices of TQM and three practices of HRM are integrated in an organized manner to examine the influence of TQM and HRM practices on KM activities. Findings – These findings provide a basis for developing a model to advance the HRM, TQM and KM research literature. Practical implications – The practical implication of this study could be useful for business managers, who want to enhance organizational KM activities through implementing HRM and TQM practices that support their organization’s KM efforts. Originality/value – This paper makes a significant contribution by developing an integrated HRM and TQM model as a methodological example which can be useful for tracking the degree of HRM and TQM effects on KM activities. Organizations could use this framework to do a pre-test baseline measurement, and then periodically re-assess the effects of any HRM and TQM change.